Artisani ice cream : a taste for growth - Lara, Matilde Sousa (2012)
The motivation for this dissertation was to write a business strategy case study about a Portuguese-based company that is still in the early stages of its expansion process. The chosen company was Artisani, which entered the artisanal ice cream market in 2009 and is currently investigating several alternatives to understand which strategy it should follow in order to further its growth. The company has to decide how best to expand its business activity without damaging its high quality brand image. After the Case Study, the dissertation presents a Literature Review. This chapter includes suggested concepts, frameworks and tools that are useful in analyzing the Case Study. The Literature Review is followed by the Teaching Note, which includes an extensive analysis of the case and proposes recommendations for the company’s future expansion strategy. This chapter establishes a connection between the Case Study and the theory presented in the Literature Review section. From the case analysis, it can be concluded that the franchising option could be the best alternative for the business’s future expansion since the company would be able to grow at a fast pace, extend its area of influence and reach wider market coverage without incurring in huge investments. Nevertheless, Artisani’s owners have to be extremely careful because in order to have sustainable growth, the firm must continue to transmit a coherent and homogeneous message to all its clients.